Reading Gestures in Valentin de Boulogne’s Paintings - Maurice Géracht (Interfaces)
This article is a close reading of the gestures in selected paintings by Valentin de Boulogne exhibited at The New York Metropolitan Museum of Art October 7, 2016 – January 16, 2017. The gestures are impelled by body motions, dramatic actions, as well as props, and fall into three categories: descriptive; rhetorical; and symbolic.